A matemática em livros didáticos estadunidenses e brasileiros: uma análise sobre o ensino de logaritmos - Rosa, Crístiam Wallao (2015)
The aim of this study is to investigate the similarities and differences regarding the methodological approach found in USA and Brazilian textbooks dealing with logarithms. For this purpose we researched on twenty-two textbooks of Mathematics that addressed such content. At first we carried out a historical overview about logarithms since its invention by Napier in 1614 through his work Mirifici Logarithmorum Canonis Descriptio, also considering the collaboration by other great mathematicians like Bürgi and Briggs. After, we carried on an analysis of textbooks research by means of a bibliographical search, qualitative and descriptive according to Gil (2002), and on a second moment, the principles of Bardin content analysis (2011). As a result of the analysis we concluded that USA books are more well founded and focused on learning, especially from 1980 onward, having a much larger number of examples and exercise, by direct application, settings, properties, or contextualized in some way. However, the Brazilian books are geared toward classical education without many examples, being quite direct.